Theory of mind in patients with mild cognitive impairment: A systematic review - Morellini, Lucia; Izzo, Alessia; Ceroni, Martino; Rossi, Stefania; Zerboni, Giorgia; Rege-Colet, Laura; Biglia, Elena; Sacco, Leonardo (Frontiers in Psychology, 2022)
The focus of this systematic review was to collect and align studies which analyze the functionality of theory of mind (TOM) in patients with mild cognitive impairments (MCI). Especially, we identified 20 papers published between 2012 and 2022 which meet inclusion criteria. Papers search, selection, and extraction followed the PRISMA guidelines. In order to summarize data from papers, we used a narrative synthesis approach. Results display, that in 18 papers out of 20, theory of mind (TOM) is impaired in all types of MCI patients – which depend on different etiology and way to diagnose –. Only 2 out of 20 did not reported significant differences in TOM performance between MCI patients and healthy control. The review had also the aim to bundle the variety type of tasks used by the author to assess multiple domains of TOM. This heterogeneity does not allow us to make a comprehensive comparison between the results, so we suggest the need to align the results using the same type of tests and TOM assessment. In the end, our work highlights also 2 neuropsychological studies which confirm the most of results - due to the objective approach adopted to investigate this topic - and suggest exploring more this point of view in future research.